Legal Protection Against Victims of Illegal Online Loan Users (Universitas Negeri Semarang, 2021)
Online loans are currently increasingly widely circulated in the community. With all the conveniences offered, this has become one of the drivers of increasing online loan users. However, there are still many illegal online loans that are widespread and increasingly difficult to control. The existence of illegal online loans causes huge losses for its users. The existence of online loans cannot be controlled and can cause problems with great impact for the victims. The importance of education and introduction to the types of online loans that are still under the auspices of the Financial Services Authority (OJK) to minimize the increase in the number of victims which has been increasing in recent times.